Analysis of Leakage Model of All-Metal Screw Pump. (27th May 2020) - Zhang, Heng; Wu, Xiaodong; An, Yongsheng
Abstract : Traditional rubber screw pumps use an interference method to engage. When the pressure is less than the breakdown pressure of the pump, there is no leakage in the pump. The all-metal screw pump stator and rotor are made of metal, and the stator and rotor adopt a gap-fitting engagement method, so even when the pump is working normally, the leakage is objective. Based on the concentric annular gap flow, the pressure drop leakage caused by the fluid inertia force is fully considered, and the calculation formula of the leakage of the all-metal screw pump is studied from the three aspects of transverse leakage, longitudinal leakage, and oblique leakage. This model was experimentally verified by a commercial all-metal screw pump produced by Shihong Petroleum Equipment Company. The model results show that the leakage of the all-metal screw pump is mainly affected by the structure parameters of the pump itself and the density of the pumped fluid, and the gap height is the main factor affecting the leakage.